Early risk factors for depression, anxiety and post-traumatic distress after hospital admission for unintentional injury: multicentre cohort study - Kendrick, Denise; Baker, Ruth; Hill, Trevor; Beckett, Kate; Coupland, Carol; Kellezi, Blerina; Joseph, Stephen; Barnes, Jo; Sleney, Judith; Christie, Nicola; Morriss, Richard (Elsevier, 2018)
Objective: To quantify psychological morbidity and identify baseline factors associated with depression, anxiety and post-traumatic distress symptoms up to 12 months post-injury.